2020
DOI: 10.1039/c9qm00698b
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the mechanical bond for molecular recognition and sensing of charged species

Abstract: This review presents progress in the field of MIM hosts for ion recognition and sensing since 2014, focusing on the synthetic approaches employed and mechanisms of host–guest binding and detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 98 publications
0
45
0
Order By: Relevance
“…Interlocked molecules, [1][2][3][4][5] such as rotaxanes and catenanes, contain cavities within which donor atoms can be positioned to bind metal ions. [6][7][8][9][10][11][12][13] Indeed, some of the first observations of the properties of the mechanical bond, including its ability to kinetically stabilize metal complexes, 6,[14][15][16][17][18] were made by Sauvage and co-workers over 30 years ago. [19][20][21] More recently, 22 we demonstrated that rotaxanebased ligands can be used to produce complexes the non-interlocked equivalent of which are inaccessible, including examples reminiscent of the distorted "entatic states" of metalloproteins, 23,24 suggesting that interlocked ligands could allow engineering of the properties of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Interlocked molecules, [1][2][3][4][5] such as rotaxanes and catenanes, contain cavities within which donor atoms can be positioned to bind metal ions. [6][7][8][9][10][11][12][13] Indeed, some of the first observations of the properties of the mechanical bond, including its ability to kinetically stabilize metal complexes, 6,[14][15][16][17][18] were made by Sauvage and co-workers over 30 years ago. [19][20][21] More recently, 22 we demonstrated that rotaxanebased ligands can be used to produce complexes the non-interlocked equivalent of which are inaccessible, including examples reminiscent of the distorted "entatic states" of metalloproteins, 23,24 suggesting that interlocked ligands could allow engineering of the properties of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Interlocked molecules[ 1 , 2 , 3 , 4 , 5 ] contain cavities within which donor atoms can be positioned to bind metal ions. [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] Indeed, some of the first observations of the properties of the mechanical bond, including its ability to kinetically stabilize metal complexes,[ 6 , 14 , 15 , 16 , 17 , 18 ] were made by Sauvage and co‐workers over 30 years ago. [ 19 , 20 , 21 ] More recently, [22] we demonstrated that rotaxane‐based ligands can be used to produce complexes the non‐interlocked equivalent of which are inaccessible, including examples reminiscent of the distorted “entatic states” of metalloproteins,[ 23 , 24 ] suggesting that interlocked ligands could allow engineering of the properties of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Interlocked molecules [1–5] contain cavities within which donor atoms can be positioned to bind metal ions [6–13] . Indeed, some of the first observations of the properties of the mechanical bond, including its ability to kinetically stabilize metal complexes, [6, 14–18] were made by Sauvage and co‐workers over 30 years ago [19–21] .…”
Section: Introductionmentioning
confidence: 99%